Perancangan Aplikasi Pembelajaran Tajwid Berbasis Android Menggunakan Metode Extreme Programming - Awaludin, Mahmud; Hidayat, Muslim; Asnawi, Muhammad Fuat; Sibyan, Hidayatus (STMIK Banjarbaru, 2024)
Mastering the science of Tajwid is an obligation for every Muslim, as Allah SWT says in the Qur'an, Surah Al-Muzzammil verse 4: